Infant Feeding Practices, Prevalence of Adolescent Motherhood and Malnutrition among Infants in Mangu Local Government Area, Plateau State, Nigeria - Aloysius N. Maduforo; Clementina E. Okoro; Justina N. Chikwendu; Chika Ndiokwelu; Gift Asogwa; Miracle C. Aloysius-Maduforo; Chinyere C. Okwara; Josephine Nwanneoma Okorie (Ubiquity Press, 2024)
Background: Adolescent motherhood and malnutrition among children are significant challenges in Africa, but there is limited data on the impact of adolescent motherhood on their children's health and nutrition. This study assessed infant feeding practices, prevalence of adolescent motherhood, and malnutrition among infants in Mangu local government area (LGA). Methodology: A cross-sectional survey using multistage sampling was conducted. Validated questionnaires were used to collect socio-demographic data, and appropriate tools were used for anthropometric measurements. Data were compared with established standards. Descriptive statistical tools, chi square, Pearson correlation, and independent sample t-test were used for data analysis, with significance set at p < 0.05. Results: A total of 200 mothers completed the study. The majority of the infants (78.5%) were less than 6 months old, and 21.5% were 6-12 months old. Breastfeeding initiation within 1 hour was reported by 39% of mothers, while 38% practiced prelacteal feeding. Only 28.5% practiced exclusive breastfeeding, and all mothers breastfed their babies. The prevalence of adolescent motherhood was 37.5%. The prevalence of stunting, wasting, and underweight among infants were 29.5%, 12%, and 8.5%, respectively. Children of adolescent mothers had higher rates of severe stunting compared to children of mothers above 19 years of age. There were significant differences (p = 0.017 and p = 0.029) in stunting rates and weight-for-age indices between children of adolescent mothers and mothers above 19 years of age. Conclusion: Adolescent motherhood contributes to chronic malnutrition in children, and there is a high prevalence of malnutrition among infants in Mangu LGA, Plateau State.